2005
DOI: 10.1111/j.1747-0765.2005.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Species on CH4and N2O Fluxes from a Volcanic Grassland Soil in Nasu, Japan

Abstract: To investigate the effects of plant species in grassland on methane (CH4) and nitrous oxide (N2O) fluxes from soil, fluxes from an orchardgrass (Dactylis glomerata L.) grassland, white clover (Trifolium repens L.) grassland and orchardgrass/white clover mixed grassland were measured weekly from April 2001 to March 2002 using a vented closed chamber method. Related environmental parameters (soil inorganic N content, soil pH (H2O) value, soil moisture content, soil temperature, grass yield, and the number of soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 26 publications
4
36
2
Order By: Relevance
“…3 and 4) suggest that soybean nodules formed with B. japonicum carrying nos genes scavenge N 2 O in soil, thus lessening N 2 O emission to the atmosphere from soybean fields. However, several groups have reported that cultivation of legume crops often enhances N 2 O emission from fields of alfalfa (11), soybean (51), white clover (36), and Bengal gram (16). Thus, we want to discuss the N 2 O paradox of legume root nodules for those results and ours.…”
Section: Discussionmentioning
confidence: 97%
“…3 and 4) suggest that soybean nodules formed with B. japonicum carrying nos genes scavenge N 2 O in soil, thus lessening N 2 O emission to the atmosphere from soybean fields. However, several groups have reported that cultivation of legume crops often enhances N 2 O emission from fields of alfalfa (11), soybean (51), white clover (36), and Bengal gram (16). Thus, we want to discuss the N 2 O paradox of legume root nodules for those results and ours.…”
Section: Discussionmentioning
confidence: 97%
“…Generally, uptake of CH 4 occurs in unfertilized grasslands. Mori et al (2005) reported CH 4 uptake (À1.8 kg C ha À1 yr…”
Section: Discussion Ch 4 Emissionsmentioning
confidence: 99%
“…A previous study reported that ammonium-based fertilizer inhibited CH 4 oxidation, whereas the application of farmyard manure that contained more N than the fertilizer had no inhibitory effects (Powlson et al 1997). However, CH 4 flux is controlled by soil moisture, soil temperature, soil pH and plant species, as well as by application of fertilizer (Mosier et al 1991;Mosier et al 1996;Powlson et al 1997;Kammann et al 2001;Le Mer and Roger 2001;Mori et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural land is one of the major sources of N 2 O (8,12,23). In particular, more N 2 O is emitted from agricultural fields with legume crops than from fields with nonlegume crops (5,11). Kim et al (10) found that N 2 O emission from fields with nodulating soybean was several times higher than that from fields with nonnodulating soybean at a flowering stage of soybean growth in the field, suggesting that nodulation enhanced N 2 O emission.…”
mentioning
confidence: 99%